2006
DOI: 10.1111/j.1743-6109.2006.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Candesartan and Hydralazine in the Protection of Penile Structures in Spontaneously Hypertensive Rats

Abstract: Introduction Previous studies indicate that angiotensin type I receptor antagonists present a beneficial effect on penile structures in hypertensive rats. However, at present there is no substantial information concerning the functional aspect of this class of antihypertensive drugs. Aim To determine, by in vitro studies, functional effects of Candesartan in comparison with a traditional vasodilating agent, Hydralazine, on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…Moreover, AT1 activation mediates an increase in RhoA/ Rho-kinase activity and a decrease in eNOS protein expression, which can be readily reversed by the AT1 antagonist losartan (Jin 2009). This effect is specifically related to Ang II, which is supported by the finding that other antihypertensive agents did not improve erectile function (Toblli et al 2004a;Mazza et al 2006). Similar findings have been demonstrated in rat models of agerelated ED (in normotensive animals), with losartan improving eNOS protein expression and erectile function (Park et al 2005a), and in diabetic ED-with improvement following valsartan administration.…”
Section: Local Renin-angiotensin Systemssupporting
confidence: 78%
“…Moreover, AT1 activation mediates an increase in RhoA/ Rho-kinase activity and a decrease in eNOS protein expression, which can be readily reversed by the AT1 antagonist losartan (Jin 2009). This effect is specifically related to Ang II, which is supported by the finding that other antihypertensive agents did not improve erectile function (Toblli et al 2004a;Mazza et al 2006). Similar findings have been demonstrated in rat models of agerelated ED (in normotensive animals), with losartan improving eNOS protein expression and erectile function (Park et al 2005a), and in diabetic ED-with improvement following valsartan administration.…”
Section: Local Renin-angiotensin Systemssupporting
confidence: 78%
“…Histological studies demonstrated lower content of cavernosal and vascular smooth muscle as well as type III collagen in candesartan treated rats as compared to untreated controls and hydralazine treated rats [13]. A similar 6 month study comparing the calcium channel blocker amlodipine to the ARB losartan was revealing of similar antihypertensive efficacy between the drugs; however, losartan treated rats had diminished cavernosal and vascular smooth muscle as well as type III collagen, an effect that was not observed in the amlodipine treated rats.…”
Section: Animal Studies On Arbmentioning
confidence: 91%
“…The impairment of NOS and NO availability should lead to develop ED (30,36). Mazza et al reported that treatment with an ARB, candesartan, improved cavernous sinusoidal eNOS and acetylcholine-induced hypo-relaxation in the SHR (25). Angiotensin II is locally produced and secreted from penile endothelial cells and smooth muscle cells (18).…”
Section: Enos and Nnos Mrnas In The Rat Penile Tissuesmentioning
confidence: 99%
“…Also, hypertrophy of corpus cavernous smooth muscle and vascular smooth muscle has been confirmed in the SHR (32). In previous studies, the protective effect of ARB, such as losartan and candesartan, was already investigated in the penis in the SHR (9,25). Olmesartan medoxomil (olmesartan) is a newer ARB than losartan, and more effective to antagonize the AT1R (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation